2019
DOI: 10.1093/nar/gkz703
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Class 2 OLD family nucleases supports a two-metal catalysis mechanism for cleavage

Abstract: Overcoming lysogenization defect (OLD) proteins constitute a family of uncharacterized nucleases present in bacteria, archaea, and some viruses. These enzymes contain an N-terminal ATPase domain and a C-terminal Toprim domain common amongst replication, recombination, and repair proteins. The in vivo activities of OLD proteins remain poorly understood and no definitive structural information exists. Here we identify and define two classes of OLD proteins based on differences in gene neighborhood and amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 59 publications
5
66
1
Order By: Relevance
“…Based on sequence homology, the OLD family proteins are the closest to GajA among characterized nucleases ( Figure S11). BpOLD and TsOLD also consist of an ATPase domain and a TOPRIM domain, resembling the domain organization of GajA (19,20). As previously reported, the ATPase domain of TsOLD is functional in ATP hydrolysis and the TOPRIM domain carries out non-specific nuclease activity (20).…”
Section: Gaja Functional Domainssupporting
confidence: 57%
See 2 more Smart Citations
“…Based on sequence homology, the OLD family proteins are the closest to GajA among characterized nucleases ( Figure S11). BpOLD and TsOLD also consist of an ATPase domain and a TOPRIM domain, resembling the domain organization of GajA (19,20). As previously reported, the ATPase domain of TsOLD is functional in ATP hydrolysis and the TOPRIM domain carries out non-specific nuclease activity (20).…”
Section: Gaja Functional Domainssupporting
confidence: 57%
“…The Gabija system exists in about 8.5% of all sequenced bacteria and archaea (10). In most cases it consists of two components, GajA and GajB, while in some cases the GajB predicted as a helicase is absent (10,19,20). Bioinformatics analysis indicated that GajA contains an ATPase-like domain (residues 1-341) and a TOPRIM domain (residues 348-510) ( Figure 1A).…”
Section: Gaja Exhibits Specific Cleavage Activity In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of a mutation is predicted using the PAO1-UW genome as a reference. In case of PA2492 (mexT) the nucleotide changes are proposed to alter the start codon and hence the sequence of N-terminal part (OLD) family nuclease containing an N-terminal ATPase domain and a C-terminal TOPRIM domain [52,53]. Since OLD proteins can act as exonucleases digesting DNA in the 5′-3′ direction as well as endonucleases acting on supercoiled, circular DNA substrates [53], it was tempting to speculate that PA1939 could play a role in degradation of the foreign DNA in concert with PA2735 acting as methylase.…”
Section: Analysis Of Pao1161 Revertants In Pa1939 and Pa2735mentioning
confidence: 99%
“…Structural comparison of the M5 NTD with the Burkholderia pseudomallei OLD (BpOLD) protein (PDB 6NK8), which cleaves one strand of a DNA duplex using a catalytic Toprim domain (Schiltz et al, 2019), reveals a common spatial organisation of active-site acidic residues ( Figure 5B). Like BpOLD, M5 has a strictly conserved Toprim catalytic triad E10/D56/D58 (D58 here mutated to A), and additional conserved, acidic residues (D14, E96), that are positioned for coordination of two Mg 2+ ions ( Figure 5B).…”
Section: Cryoem Structure Of the M5/50s(pre-5s) Complexmentioning
confidence: 99%